APLlKASI PEMBERIAN ZAT PENGATUR TUMBUH PMDATANAMAN CABAl KECIL YANG DITANAM DI MUSIM HUJAN - Koentjoro, Yonny (MAPETA, 2008)
High percentage of fall ing of flower and fruit of chilli plant in rainy season represents problems which often occurs so that productivity of chilli very low in the rainy season and often caused failure on fruit set. The aim of this research is knowing the influence of plant regulator in increasing the productivity of chilli plant which is cultivated at off season (rainy season). This research was designed using Random Block Design which consist of 2 factors. The first factor is Ethrel with 4 levels giving; 0 ppm / I, 250 ppm / I, 500 ppm / I and 1000 ppm / I and the second factor is Dekamon with also 4 levels giving; 0 cc / I, 0.5 cc / I, I cc / I and 2 cc / 1. Results of research indicate that the plant growth regulator application Dekarnon and Ethrel effecting on all variables observed both generati ve and vegetative variables, in general, at all levels of concentration of the plant growth regulator which is applied result the linier positive influence. Research also shows there is no influence significantly of the interaction between the two plant growth regulator. Key words: Zat pengatur tumbuh, musim hujan, cabai kecil